Methane concentration in Allan Hills ice cores ... - Bender, Michael; Brook, Edward J; Higgins, John; Yan, Yuzhen (U.S. Antarctic Program (USAP) Data Center, 2019)
This file includes the concentration methane (CH4) in Allan Hills ice cores (ALHIC1502 and ALHIC1503). ...